The Value of Holiness in Popular Culture: A Christian Perspective on Music, Film, and Social Media - Sitanggang, Ariani (Cattleya Darmaya Fortuna, 2025)
The rapid development of popular culture, particularly through music, films, and social media, influences the way society, especially the younger generation, forms values ​​in everyday life. This phenomenon poses a challenge for Christians in maintaining and implementing the values ​​of holiness taught by the Bible. This study aims to analyze how the Christian perspective responds to the influence of popular culture and strategies for instilling values ​​of holiness in social interactions and modern media consumption. The method used is a qualitative approach with a literature study approach and content analysis of music, films, and social media materials popular in society. The results of the study indicate that although popular culture tends to present secular content, there are opportunities to integrate values ​​of holiness through wise content selection, spiritual reflection, and active involvement in Christian communities. This study provides insights for churches, educators, and parents in guiding the younger generation to continue living according to the principles of the Christian faith amidst the complex flow of popular culture.